أثر الخبرة المهنية للمراجع الخارجي في تخفيض المخاطر المالية: دراسة ميدانية على شركة معاوية البرير الصناعية - إسماعيل، نمارق أزهري أحمد; الأمين، الشريف الحسين عوض (جامعة النيلين - كلية التجارة, 2019)
هدفت الدراسة إلى بيان دور الخبرة المهنية للمراجع الخارجي في الحد من المخاطر التي تتعرض لها الشركات الصناعية في مجال عملها الصناعي والمالي. تمثلت مشكلة الدراسة في المخاطر المالية الناتجة من طبيعة العمل الخاصة بتلك الشركات من الناحية التشغيلية ومن الناحية المالية، حيث استخدم الباحثان استمارة استبانة على العاملين بشركة معاوية البرير، توصلت الدراسة إلى أن الخبرة المهنية للمراجع الخارجي ساهمت بصورة إيجابية في تخفيض مخاطر السيولة، كما ساهمت الخبرة المهنية في الحد من مخاطر التشغيل بالمنشآت الصناعية. وأوصت هذه الدراسة بالتدريب المستمر للمراجعين لتفادي مخاطر السيولة والتي تؤثر سلبا على نشاط المنشأة، بالإضافة إلى العمل على استمرار تنمية وتطوير الخبرة المهنية لأعضاء مهنة المحاسبة والمراجعة من خلال الاهتمام بالدورات التدريبية المستمرة. The study aimed to show the role of the professional experience of the external auditor in reducing the risks that industrial companies are exposed to in the field of their industrial and financial work. The problem of the study was represented in the financial risks resulting from the nature of the work of these companies from an operational and financial point of view, where the researchers used a questionnaire form on the employees of Muawiya Al-Barer Company, the study concluded that the professional experience of the external auditor contributed positively to reducing liquidity risks, and the experience also contributed Professional in reducing the risks of operating in industrial facilities. This study recommended continuous training of auditors to avoid liquidity risks, which negatively affect the activity of the facility, in addition to working on the continued development and development of professional experience for members of the accounting and auditing profession through paying attention to continuous training courses.
Keywords: مراجعة الحسابات -- التدقيق الخارجي -- إدارة المخاطر -- المؤسسات الصناعية -- السودان